2016
DOI: 10.1038/nchem.2518
|View full text |Cite
|
Sign up to set email alerts
|

Diindeno-fusion of an anthracene as a design strategy for stable organic biradicals

Abstract: The consequence of unpaired electrons in organic molecules has fascinated and confounded chemists for over a century. The study of open-shell molecules has been rekindled in recent years as new synthetic methods, improved spectroscopic techniques and powerful computational tools have been brought to bear on this field. Nonetheless, it is the intrinsic instability of the biradical species that limits the practicality of this research. Here we report the synthesis and characterization of a molecule based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
324
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(339 citation statements)
references
References 47 publications
14
324
1
Order By: Relevance
“…In fact, although the present study has focused on a class of quasi-1D polyaromatic systems, they exhibit the feature of localizing the radical spin states in the zigzag boundaries commonly observed in many other extended PAHs, for which the present results can be directly transferred. However, there are other classes of PAHs such as zethrenes or diindeno[b,i]anthracenes 57,58 to name a few, where the analysis of reactive centers is not so clear and where calculations as the ones presented here will provide important support by pinpointing the most chemically reactive centers and tuning their native radical structures through the introduction of donor or acceptor hetero-atomic defects in the carbon skeleton. Thus, the tunability of the diradical character of the acenes demonstrated in the present study through chemical substitutions is a potential route to be explored for designing organic molecules with enhanced nonlinear optical activity 59,60 or with optimized efficiency for singlet fission process in organic photo-voltaic devices 61,62 while retaining the feasibility of chemical synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although the present study has focused on a class of quasi-1D polyaromatic systems, they exhibit the feature of localizing the radical spin states in the zigzag boundaries commonly observed in many other extended PAHs, for which the present results can be directly transferred. However, there are other classes of PAHs such as zethrenes or diindeno[b,i]anthracenes 57,58 to name a few, where the analysis of reactive centers is not so clear and where calculations as the ones presented here will provide important support by pinpointing the most chemically reactive centers and tuning their native radical structures through the introduction of donor or acceptor hetero-atomic defects in the carbon skeleton. Thus, the tunability of the diradical character of the acenes demonstrated in the present study through chemical substitutions is a potential route to be explored for designing organic molecules with enhanced nonlinear optical activity 59,60 or with optimized efficiency for singlet fission process in organic photo-voltaic devices 61,62 while retaining the feasibility of chemical synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The best performing semiconductor among the structures of Figure is evidently TIPS PEN 25 , with independently reproduced hole mobility µ = 1.5–1.7 cm 2 V −1 s −1 . Then come Ph2‐IDPL 27 , DIAn 28 , FDT 29 , and FDT‐Br 30 with µ = 0.7, 10 −3 , 10 −5 , and 10 −5 cm 2 V −1 s −1 . The scare data and the issue of stability preclude to reach reliable conclusions about an eventual link between mobility and diradical character.…”
Section: Charge Transportmentioning
confidence: 99%
“…It was elucidated in detailed experimental and theoretical studies that this cyclopenta-fused PH possesses an open-shell singlet biradical structure in the ground state and exhibits high stability under ambient conditions (t 1/2 = 39 days). [6][7][8][9] Moreover, most of these planar structures show closed-shell characteristics in the ground state.Previous studies have revealed that not only aromaticity,b ut also geometry played an important role in determining the electronic structures of PHs. UV/Vis spectral measurements revealed that the title molecule has avery narrowoptical energy gap of 0.92 eV,w hichi sc onsistent with the electrochemical analysis and further supported by density functional theory (DFT) calculations.…”
mentioning
confidence: 99%
“…[1] Several types of open-shell PHs have been constructed by using bisphenalenyl, [2] zethrene, [3] and anthene [4] building blocks.F urthermore,m uch effort has been devoted to the synthesis of stable diindeno-based PHs by fusing two indene units into a p-conjugated bridge, [5] owing to their narrow energy gaps,the singlet fission phenomenon, and their potential proaromatic features. [6][7][8][9] Moreover, most of these planar structures show closed-shell characteristics in the ground state.Previous studies have revealed that not only aromaticity,b ut also geometry played an important role in determining the electronic structures of PHs. [6][7][8][9] Moreover, most of these planar structures show closed-shell characteristics in the ground state.Previous studies have revealed that not only aromaticity,b ut also geometry played an important role in determining the electronic structures of PHs.…”
mentioning
confidence: 99%